Does Security Imply Safety? On the (Lack of) Correlation Between Different Aspects of Security. Issue 1 (15th July 2015) - Rigterink, Anouk S.
This paper investigates to what extent different aspects of security correlate. It distinguishes four concepts covered by the term 'security': technical safety, perceived safety, technical security and perceived security. It is shown that these concepts need not correlate conceptually. Furthermore, the paper shows empirically that these concepts correlate weakly in two cases. This has implications for policy and research. First, it leaves open the possibility that interventions targeting one aspect of security do not affect, or even adversely affect, another aspect of security: an expression of a security gap. Second, research is commonly motivated by individual-level arguments relating to safety, whilst relying on aggregate indicators more likely capturing security.